A Pellucid approach for PBL using Advanced Mind Mapping - Alok, Govil; Govil, Vidushi; Srikar, K.; Srujana Reddy, V.; Lohith, M. (Journal of Engineering Education Transformations, 2021)
Engineering education has been revamping its curriculum and teaching methods lately to accompany innovation engineering to aid the fourth industrial revolution. In order to bring efficacious outputs among engineering students and setting up benchmarks in a technological environment to grow as an entrepreneur, a new effective and efficient curriculum infusing design, engineering and technology is sustainably developed. The study explores various dimensions of innovative curriculum and its role in nurturing freshman’s perspectives in engineering and its applications are projected using activitybased methods to develop their cognitive psyche. Among many tools, mind mapping has provided a lucid illustration, both in visual and cognitive aspects. These tools were explored in a course introduced in the third year as design thinking and innovation for about 42 students. The primary focus has been to impart design thinking skills thereby making them visionary with a wider perception. The effectiveness of the course was assessed by the surveys and feedbacks and the efficiency from the results obtained by considering pre and post classroom activities. Mind mapping is considered as one of the simplest tools which can be used from primary to master level with ease. The intent of the students and ideations itself prove the efficacy of the tool and its importance in education.